Energy efficient network protocols for wireless sensor networks - Forest, Vincent. (2012)
Due to limited energy resources in Wireless Sensor Networks, network lifetime has been important concern in designing network protocols. In recent years, energy-harvesting, converting ambient energy to electrical energy, has emerged as an alternative to power sensor nodes. By leveraging on energy-harvesting, new solution strategies could be designed for problems that arise in these areas. Several energy harvesting aware routing protocols have been proposed to deal with sensor networks with energy harvesting capabilities. One of them is the Energy Neutral Routing Protocol (ENER) with novel energy harvesting management mechanism which was proposed to maintain the network in an energy neutral state with maximized energy efficiency. Simulations show that the proposed protocol can also improve the distinct packet delivery ratio while maintaining the energy neutrality of the network. This project therefore aims to further investigate the performance of proposed protocol with different MAC layers, namely CSMA and SMAC. The performances to be investigated are energy consumption fairness by examining the residue of battery level at the end of the operation cycle, distinct packet delivery ratio and average packet delivery delay. The simulations will be done in OMNeT++ (a network simulation framework) and comparison of the results between simulation with CSMA protocol and simulation with SMAC protocol will be presented in chapter 4. The conclusion and future recommendation are subsequently presented in chapter 5.